2016
DOI: 10.3892/mmr.2016.4844
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide reduces proliferation and enhances apoptosis of human non-small cell lung cancer cells through PTEN by targeting miR-21

Abstract: Triptolide is used in traditional Chinese medicine. It has the advantages of a unique mechanism of action, a wide antitumor spectrum, multiple targets, multi-channel effects and low toxicity. The current study was conducted to evaluate whether the potential anticancer effects of triptolide reduces proliferation and enhances apoptosis of human non‑small cell lung cancer (NSCLC) cells, and to assess the underlying anticancer mechanisms. In PC‑9 cells, treatment with triptolide reduced cell proliferation and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Previous studies had shown the roles of tumor-derived miR-21 in multiple steps of tumor progression, including tumor growth at primary and secondary sites, invasion, migration, and extracellular matrix modification. MiR-21 promoted tumor growth by repressing many tumor suppressor genes, including PTEN, 8,9 /CDK2AP1, 15 and B-cell translocation gene-2 (BTG-2), 16 and inhibiting B-cell lymphoma-2 (BCL-2), 17 an apoptosis gene. MiR-21 also increased cell motility and invasion by down-regulation of metastasis-related tumor suppressor genes, including maspin and programmed cell death 4 (PDCD4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown the roles of tumor-derived miR-21 in multiple steps of tumor progression, including tumor growth at primary and secondary sites, invasion, migration, and extracellular matrix modification. MiR-21 promoted tumor growth by repressing many tumor suppressor genes, including PTEN, 8,9 /CDK2AP1, 15 and B-cell translocation gene-2 (BTG-2), 16 and inhibiting B-cell lymphoma-2 (BCL-2), 17 an apoptosis gene. MiR-21 also increased cell motility and invasion by down-regulation of metastasis-related tumor suppressor genes, including maspin and programmed cell death 4 (PDCD4).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 targets PTEN in lung cancer cells and hepatocellular cancer cells to enhance their proliferation and reduce apoptosis. 8,9 Very recently PTEN has been shown to play an important role in osteoclast differentiation. 10,11 To further validate our prediction, we performed another crossculture of peripheral blood monocytes and plasma from lung cancer patients with the intervention of exogenous miR-21 Figure 2 The characteristically higher miR-21 level in the plasma of BM patients.…”
Section: Circulating Mir-21 Affected Pten To Promote Osteoclastogenesismentioning
confidence: 99%
“…In particular, miR-21 targets multiple genes in mTOR pathway, including PTEN, p85α and PDCD4. Besides promoting malignant growth, the miR-21/PTEN/PI3K/AKT/mTOR axis has been shown to influence anti-cancer effects of zoledronic acid [80] , triptolide [81] , Metformin [82] , Matrine [83] and curcumin [84] , and modulate radiosensitivity [85, 86] and chemosensitivity to tamoxifen, fulvestrant [87] , sorafenib [88] , cisplatin [89, 90] , imatinib [91] , gefitinib [92] , doxorubicin [93] , daunorubicin [94] , anti-EGFR tyrosine kinase inhibitors (TKI) [95] and the CHOP chemotherapy regimen [96] . miR-21 also influences PI3K/AKT/mTOR signaling via PIK3R1 that negatively regulates p110 subunit under certain circumstances.…”
Section: Mirnas That Activate Mtor Pathwaymentioning
confidence: 99%
“…The incidence of lung cancer nearly doubled in China over the past ten years. To date, advanced achieve-NAIZHI WANG 1 TAO FENG 1 XIAONA LIU 1 QIN LIU 2, * ment has been made in the treatment of NSCLC. However, many patients with NSCLC are presented with metastasis to existing treatments, such as chemotherapy, radiotherapy and surgery (1).…”
mentioning
confidence: 99%